A review of production protocols used in producing economically viable monosex tilapia - Francis, Nwachi Oster; Esa, Yuzine (Academic Journals, 2016)
In the culture of tilapia seed various issues come into play tilapia when stocked in pond multiply excessively resulting in unhealthy competition for food and natural resources leading to a large number of stunted growths and a large number of mini fish that is not economically viable sexual diamophisim which means that the male fish grow bigger than the female in a mixed culture production, this results in culturists wanting only the seed of the male fish or ways that the sex of fish seed produced is skewed towards masculine fish. Culturist and farmers acknowledged the use of single sex fish also known as monosex fish as solution to the problem. The production of single sex fish which in the case of tilapia all male fish also has its own setback based on the production methods used in this case farmers ability to use the available resources in achieving the basic aim of production is a necessity. Monosex fish has the ability to tolerate sever environmental conditions including temperature, salinity low dissolve oxygen, greater uniformity of size is achieved at harvest because none of the fish is wasting energy in gonadal development. The various method used in producing monosex is based on the ability of the culturist to manage the structures (Pond, tanks) consumables (Hormones), systems (Water re-use, stagnant water) and skilled personal in producing and managing the production processes. In every step of production care is required because the production is gender specific pure breed most be used and strain confirm using current method of identification. INTRODUCTION The life history of the fish tilapia is made up of two distinct ability: Reproduction in captivity a virtue that has a positive and negative aspect (Nwachi, 2013). This characteristics of tilapia makes it a fish, farmers want to culture because of the fact that there will not be need for them to continually go back to procure fish seed after each circle of production at the same time this ability also results in production issue during culture. Tilapia, when stocked in pond multiply excessively resulting in unhealthy competition for food and natural resources leading to a large number of stunted growths and a large number of mini fish that is not economically viable (Campos-Mendoza et al., 2004), sexual diamophisim which means that the male fish grow bigger than the female, this results in culturists wanting only the seed of the male fish or ways that the sex of fish seed produced is skewed towards masculine fish. Monosex fish has the ability to tolerate